A Silsesquioxane Organically Modified with 4-Amino-5-(4-pyridyl)-4H-1, 2, 4-triazole-3-thiol: Thermal Behavior and Its Electrochemical Detection of Sulfhydryl Compounds. (9th July 2014) - Do Carmo, D. R.; Silvestrini, D. R.; Barud, H. S.; Dias Filho, N. L.; Bicalho, U. O.; Soares, L. A.
Abstract : The octakis(3-chloropropyl)silsesquioxane (SS) was organofunctionalized with 4-amino-5-4(pyridyl)-4H-1, 2, 4-triazole-3-thiol. The product formed (SA) was undergo another reactions in two steps, first with copper and so hexacyanoferrate (III) to form CuHSA. The organofunctionalized silsesquioxane was characterized by the following techniques: scanning electron microscopy (SEM), Fourier transform infrared (FTIR), nuclear magnetic resonance (NMR) in solid state, and thermogravimetric analysis in air and nitrogen atmosphere. The composite CuHSA was incorporated into a graphite paste electrode and the electrochemical behavior studies were conducted with cyclic voltammetry. The cyclic voltammogram of the modified graphite paste electrode with CuHSA showed one redox couple with formal potential E θ ′ = 0.75  V versus Ag/AgCl (sat) (KCl 1.0 mol L −1 ; v = 20 mV s −1 ) attributed to the redox process Fe (II) (CN)6 /Fe (III) (CN)6 of the binuclear complex formed. The redox couple presents an electrocatalytic response of sulfhydryl compounds such as n-acetylcysteine and l-cysteine. For determination of n-acetylcysteine and l-cysteine the modified graphite paste electrode showed a linear region in the concentration range of 2 to 20 mmol L −1 . The modified electrode was chemically and electrochemically stable and showed good reproducibility.